2022
DOI: 10.3390/pathogens11101140
|View full text |Cite
|
Sign up to set email alerts
|

Trained Immunity Provides Long-Term Protection against Bacterial Infections in Channel Catfish

Abstract: Beta glucan exposure induced trained immunity in channel catfish that conferred long-term protection against Edwardsiella ictaluri and Edwardsiella piscicida infections one month post exposure. Flow cytometric analyses demonstrated that isolated macrophages and neutrophils phagocytosed higher amounts of E. ictaluri and E. piscicida. Beta glucan induced changes in the distribution of histone modifications in the monomethylation and trimethylation of H3K4 and modifications in the acetylation and trimethylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Likewise, in channel catfish ( Ictalurus punctatus ), β‐glucan exposure could induce trained immunity and confer long‐term heterologous protection against bacterial infections with Edwardsiella ictaluri and Edwardsiella piscicida , as long as 1 month post‐exposure 75 . In this study, specifically, Petrie‐Hanson et al did analyse epigenetic changes in the distribution of histone modifications in monomethylation and trimethylation of H3K4, and detected modifications in the acetylation and trimethylation of H3K27.…”
Section: Trained Immunity In Teleost Fishmentioning
confidence: 90%
See 3 more Smart Citations
“…Likewise, in channel catfish ( Ictalurus punctatus ), β‐glucan exposure could induce trained immunity and confer long‐term heterologous protection against bacterial infections with Edwardsiella ictaluri and Edwardsiella piscicida , as long as 1 month post‐exposure 75 . In this study, specifically, Petrie‐Hanson et al did analyse epigenetic changes in the distribution of histone modifications in monomethylation and trimethylation of H3K4, and detected modifications in the acetylation and trimethylation of H3K27.…”
Section: Trained Immunity In Teleost Fishmentioning
confidence: 90%
“…Likewise, in channel catfish (Ictalurus punctatus), β-glucan exposure could induce trained immunity and confer long-term heterologous protection against bacterial infections with Edwardsiella ictaluri and Edwardsiella piscicida, as long as 1 month post-exposure. 75 In this study, specifically, Petrie-Hanson et al did analyse epigenetic changes in the distribution of histone modifications in monomethylation and trimethylation of H3K4, and detected modifications in the acetylation and trimethylation of H3K27. Indeed, they suggested that chromatin reconfiguration might direct trained immunity similar to what has been identified for mammals 75 ; however, the type of effector cells, how these epigenetic changes would affect these effector cells, and their direct association with β-glucan induced trained immunity remain to be elucidated.…”
Section: Trained Immunity In Food Fishmentioning
confidence: 97%
See 2 more Smart Citations